Morphology of a thermally stable small molecule OPV blend comprising a liquid crystalline donor and fullerene acceptor. Issue 27 (26th June 2019) - Bourque, Alexander J.; Engmann, Sebastian; Fuster, Allison; Snyder, Chad R.; Richter, Lee J.; Geraghty, Paul B.; Jones, David J.
Abstract : We combine thermodynamic modeling of molecular interactions in OPV blends with in situ measurements of morphology to link performance, structure and processing. Abstract : Recently organic photovoltaic (OPV) devices comprising the small-molecule liquid-crystalline donor, benzodithiophene-quaterthiophene-rhodanine (BQR), and fullerene acceptor, [6, 6]-phenyl-C71 -butyric acid methyl ester (PC71 BM), were demonstrated to achieve high performance when thermally processed, avoiding the need for slow-drying solvent additives or complex solvent-vapor annealing post-processing. In this investigation we explore the impact of thermal processing on thin film blends of BQR and PC71 BM using differential scanning calorimetry (DSC), in situ grazing incidence X-ray scattering (GISAXS, GIWAXS), and photoluminescence spectroscopy (PL) to correlate thermal behavior with morphological changes and photoactivity. We develop a phase diagram of the crystalline and liquid crystalline transitions in BQR and the related high performing electron donor material, benzodithiophene-terthiophene-rhodanine (BTR), and are able to predict phase transitions using Flory-Huggins theory, including suppression of liquid crystalline phase formation in the presence of PC71 BM. Further DSC measurements demonstrate the superior thermal stability of PC71 BM blends with BQR over blends with BTR. OPV devices with the BQR:PC71 BM active layer were prepared using the blade-coating deposition technique and exhibit optimal device performance when annealed at 120 °C for 5 min. The characteristic acceptor/donor domain size in an as-cast BQR:PC71 BM film, estimated from GISAXS, was about 60 nm which is sufficient for exciton separation. Domain purity was enhanced by annealing at temperatures above ≈80 °C. Annealing at temperatures above ≈120 °C resulted in over-coarsening of the acceptor/donor-rich phases to domain sizes beyond 80 nm and reduced performance.